Taxonomy of recent Adeonidae (Bryozoa, Cheilostomata) from Brazil, with the description of four new species - Almeida, Ana C.s.; Souza, Facelucia B.c.; Sanner, Joann; Vieira, Leandro M. (Zootaxa, 2015)
Here we present the taxonomy of the cheilostome genera Adeonellopsis MacGillivray, 1886 and Reptadeonella Busk, 1884 in Brazil. Of the six species previously reported in Brazilian waters, we include redescriptions of Adeonellopsis     subsulcata (Smitt, 1873), Reptadeonella bipartita (Canu & Bassler, 1928) and Reptadeonella costulata (Canu & Bassler, 1928). Four new species of Reptadeonella are described: Reptadeonella aspera n. sp., Reptadeonella brasiliensis n. sp. (previously misidentified as Reptadeonella violacea), Reptadeonella cucullata n. sp. and Reptadeonella leilae n. sp. Reptadeonella aspera n. sp., from Bahia State, is characterized by rugose frontal calcification, a tubular peristome, small suboral avicularium and elliptical spiramen. Reptadeonella brasiliensis n. sp. is the commonest intertidal species in NE Brazil; it is distinguished from other Brazilian Reptadeonella in having a nodular peristome, large subperistomial areolar pore and zooids with one or two frontal pores frequently replaced by a suboral avicularium and crescentic spiramen. Reptadeonella cucullata n. sp., from Espírito Santo and Bahia states, has a hood-like peristome, large subperistomial areolar pore, suboral avicularium with curved mandible and denticulate spiramen. Reptadeonella leilae n. sp., described from Bahia State, has a frontal shield with small granules, tubular peristome, semilunar to semicircular subperistomial areolar pore and circular spiramen. Diagnostic characters of Reptadeonella species are discussed.